Review of common failures in heat exchangers – Part I: Mechanical and elevated temperature failures. (January 2020) - Ali, Murad; Ul-Hamid, Anwar; Alhems, Luai M.; Saeed, Aamer
Highlights: Common failures and preventive measures are discussed. Common failure mechanisms are fatigue, creep, corrosion, and hydrogen attack. Causes of failure are fouling, scaling, salt deposition, welding, and vibration. Materials selection, operation and trained workforce controls service lifetime. Abstract: This study provides an overview of the common modes and causes of failure of heat exchanger tubes. Failure investigations of heat exchangers reported in the literature are compiled in this review based on the mechanisms of failure. A large majority of heat exchanger components fail by way of fatigue, creep, corrosion, oxidation, and hydrogen attack. Most common causes of failure include fouling, scaling, salt deposition, weld defects, and vibration. Effective recommendations to prevent such failures form an important part of this study. It is suggested that suitable materials selection, appropriate tubes design, effective control of the constitution of the working fluid and operating conditions and use of skilled workforce can prolong service lifetime of heat exchangers. Corrosion-related failures of heat exchangers are presented in a related article (Part II).